PENGARUH AGRESIVITAS PAJAK, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ 45 TAHUN 2021-2024 - Septiana Kartika Rachmawati; Justita Dura; Mohammad Bukhori (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Determining an optimal capital structure is a strategic decision for companies because it is closely related to financial risk, cost of capital, and firm value in the eyes of investors. This study aims to analyze the effect of tax aggressiveness, profitability, and firm size on capital structure in companies listed in the LQ45 Index on the Indonesia Stock Exchange for the 2021–2024 period. Capital structure is proxied by the Debt to Equity Ratio (DER), tax aggressiveness is proxied by the Effective Tax Rate (ETR), profitability is proxied by Return on Assets (ROA), and firm size is measured using the logarithm of total assets. This research employs a quantitative approach using secondary data from the annual financial statements of LQ45 companies selected through purposive sampling, and is analyzed using multiple linear regression and classical assumption tests with the aid of SPSS 26 software. The results show that, partially, profitability and firm size have a significant effect on capital structure, while tax aggressiveness does not have a significant effect. Tax aggressiveness, profitability, and firm size simultaneously have a significant effect on capital structure, indicating that these variables are able to explain the variation in capital structure of LQ45 companies during the study period. These findings are expected to serve as a reference for management, investors, and academics in evaluating financing policies and their implications for corporate financial stability and performance.